Peningkatan Kesadaran dan Pendapatan Masyarakat Melalui Rehabilitasi Mangrove dan Budidaya Ikan Nila Saline Berbasis Kemitraan - Muhaimin Hamzah; Muhammad Fajar Purnama; La Ode Alirman Afu; A Asnani; Abdul Muis Balubi; La Ode Baytul Abidin; Muhammad Trial Fiar Erawan (Universitas Muhammadiyah Parepare)
This community service activity is as a learning media for silvofishery-based mangrove rehabilitation and demonstration of tilapia saline for the prevention of ecological abrasion. In addition, to increase social awareness (preservation of coastal ecosystems) as well as alternative sources of income the people of Tobimeita Village, Konawe Utara Regency. Tobimeita Village as a location for community service (Community Service) due to the existence of active or productive farming activities and the availability of mangrove forests with the existing abrasion phenomenon due to the looting of mangrove forests for the needs of fuelwood and building materials. The potential of the farmland allows the creation of a pilot tilapia saline commodity and the implementation of silvofishery-based mangrove rehabilitation. This community service activity has a very massive effect on the social sensitivity of the community in maintaining the preservation of the coastal environment, it can be seen from the enthusiasm of all elements of the Tobimeita Village community who participated. In addition to mangrove planting activities, the demonstration plot or pilot of saline tilapia aquaculture also managed to attract the attention and interest of farmers to replicate the aquaculture activities. There is a great desire for the community to start a business through the technology of simple adaptation and acclimatization of tilapia saline. Easily adopted farming technologies and prospective tilapia commodities are key to the success of the saline tilapia demonstration plot. Specifically, these two activities provide an in-depth outcome for the people of Tobimeita Village as a constituent of community service activities.